Strategies for Continuing Professional Development of LIS Faculty in Sub-Sahara Africa - Cortez, Edwin M.; Britz, Johannes; Kigongo-Bukenya, I. M. N (Word Library and Information Congress: 74 th IFLA General Conference and Council, 2008)
The paper addresses the need for structured access to continuing education opportunities by LIS faculty in sub-Sahara Africa. The paper takes as it starting point that human development, and in particular education, lies at the heart of Africa’s sustainable development. The paper first discusses the barriers and challenges faced by LIS faculty in pursuing their professional development in the areas of teaching, research and service. A potential solution to the problem is then described in the form of an information and educational web based portal modeled after the Foundation for Professional Development, a health sector educational and development organization servicing the needs of health professionals in Southern and Eastern Africa.